RNA and liquid-liquid phase separation - Qi Guo (Non-coding RNA Research, 2021)
Liquid-Liquid Phase Separation (LLPS) is a biological phenomenon that refers to the components of similar properties form droplets condensate in cells. These droplets play an important role in maintaining the stability of order in cells. In the studies of phase separation, weak multivalent interactions between proteins have always been the focus of attentions. With the deepening research of phase separation, more and more evidences show that RNA, especially long noncoding RNA (lncRNA), also plays an important regulatory role in the phase separation. We summarized recent researches between phase separation and RNA, and focused on the function of non-coding RNA (ncRNA) in the process of phase separation. In fact, phase separation and RNA have a two-way regulation relationship. Noncoding RNA usually recruits proteins as molecular scaffolds to drive phase separation. On the other hand, phase separation is also involved in RNA transcription, transport, metabolism and other processes.